Faculty of Architecture and Fine Arts, A.F. Modrzewski Krakow University: program and teaching - Krzysztof Ingarden; Katarzyna Petri (Agathón)
Architecture, as a form of shaping space is a scientific discipline in which the interdisciplinary methods of teaching should be crucial throughout the educational process. It should be based on strong theoretical foundations and constant improvement of practical skills. Academic program developed and implemented at the Faculty of Architecture of the Andrzej Frycz Modrzewski Kraków University is in line with this philosophy. It is based on the concept of conducting the teaching process using the master class method (tutorial system). The program of the Faculty of Architecture is compliant with the educational standards for the architecture valid in Poland, while maintaining their own specificity.